Marginalized Citizens Experiences of Middle-class Moral Judgements in Communication with their GPs - Aamann, Iben Charlotte; Olesen, Birgitte Ravn (Socialmedicinsk tidskrift, 2020)
The purpose of this article is to explore how two different versions of participatory theatre give marginalized citizens living in disadvantaged areas an opposite basis for sharing experiences of being judged in communication with their GPs. The data were produced as part of a dialogic evaluation of two health communication interventions initiated by Region Zealand, Denmark. The purpose of both interventions was to invite citizens to participate in a dialogue on their experiences with their GPs, initiated through two versions of participatory theatre. The interventions were held in a range of disadvantaged areas. We used a variety of qualitative approaches such as participant observations, focus interviews and individual interviews in order to shed light on a) how the two versions of participatory theatre were developed and b) how the invitation to have a dialogue was experienced by the citizens. The analysis was conducted abductively, moving between the data production, existing research on inequality in access to health care services and theories on social inequality and its moral implications. Theoretically, we employ Bernstein´s concept of framing, Skeggs´ points about class as a relation between moral judges and judged, and perspectives on healthism, risk and responsibilization. The analysis finds that the first version of participatory theatre frames the judge-judged relation as the problem, enabling the participating citizens to share experiences of being judged as morally inferior. The framing of the second version of participatory theatre however implies the judge-judged relation, whereby the participants feel that they are being judged. As a consequence, the participants dis-identify with the role of the patient in the second version and express resentment towards health institutions. We conclude by suggesting that framing is a central perspective when researchers and health professionals wish to initiate dialogue with marginalized citizens and that the class perspective presented here is fruitful in exploring experiences of social inequality in access to health care.